2005
DOI: 10.1055/s-2005-873155
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Olanzapine and Risperidone in 367 First-Episode Patients with Non-Affective or Affective Psychosis: Results of an Open Retrospective Medical Record Study

Abstract: Despite the limitations of a retrospective MR design, study results suggest equal therapeutic efficacy of OLZ and RIS in non-affective FEP and some therapeutic advantages of OLZ compared to RIS in affective FEP patients, especially in those with acute mania. Results may serve as hypotheses for future randomised controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Lambert, in study of comparing risperidone with olanzapine in the treatment of the first episode of the affective psychosis showed somehow shorter time to reach the treatment response with olanzapine. [28] This study was open and retrospective and the difference was not significant. Hence, we think our study showed a new significant finding in the velocity of action of the risperidone compared with the other antipsychotics and this must be trialed in future studies, more.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Lambert, in study of comparing risperidone with olanzapine in the treatment of the first episode of the affective psychosis showed somehow shorter time to reach the treatment response with olanzapine. [28] This study was open and retrospective and the difference was not significant. Hence, we think our study showed a new significant finding in the velocity of action of the risperidone compared with the other antipsychotics and this must be trialed in future studies, more.…”
Section: Discussionmentioning
confidence: 94%
“…In a controlled study comparing olanzapine versus risperidone, a somehow shorter time were needed to reach the remission in olanzapine group. [28] In a controlled study comparing ziprasidone with risperidone, both agents equally improved psychotic symptom. [29] Another clinical trial compared haloperidol with olanzapine showed that two drugs didn’t have statistically different level of improvement after 24 h of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Early detection and intervention of psychotic disorders are important issues in mental health practice and research [1,2]. Different strategies have been developed to improve the detection of first episode psychosis both in the prodromal phase and during the first psychotic episode to minimize the delay of treatment after the onset of psychosis [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…As in schizophrenia (Gafoor 2010), it is unclear whether some antipsychotics are more efficacious or better tolerated in the early stages of the illness than others. In a small retrospective medical record study of firstepisode acute mania with psychosis, olanzapine was associated with better symptom remission and shorter time to remission than risperidone (Lambert 2005). Results are awaited from a recently concluded trial comparing a combination of lithium plus chlorpromazine with lithium plus olanzapine in firstepisode mania with psychotic features (http://clinicaltrials.gov/ ct2/show/NCT00202293).…”
Section: Depressive Relapsesmentioning
confidence: 99%